Ultrasound-Guided Femoral Nerve Block as an Anesthetic Alternative in the Management of Traumatic Injuries in Reconstructive Plastic Surgery in Heart Transplant Patients (Global Journal of Medical Research, 2020)
We present the clinical case of a 23-year-old male patient with a history of heart transplantation who suffered a bicycle accident presenting a bloody area in the left tibial region which was subjected to taking and applying a skin graft and allograft placement in a donor area under sedation. And ultrasound-guided femoral nerve block without presenting hemodynamic changes during the trans-anesthetic and adequate analgesia, resulting in a very useful alternative for this type of patients since they present physiologicalanatomical changes after transplantation and it is required to maintain a hemodynamic state optimal to avoid peri operative complications.